Ultrafast spin current generated by electron-magnon scattering in bulk of ferromagnets - Shin, Im-Hyuk; Min, Byoung-Chul; Ju, Byeong-Kwon; Choi, Gyung-Min (IOP PUBLISHING LTD, 2018)
The ultrafast demagnetization of metallic ferromagnets can generate a spin current in metallic nonmagnets in a ferromagnet/nonmagnet structure. Two different mechanisms for this phenomenon have been suggested: spin-dependent transport of hot electrons and spin generation by electron-magnon scattering. In this work, we optically measure a transient spin accumulation on a nonmagnetic Cu layer driven by the ultrafast demagnetization of a ferromagnet (Fe, Co, and Ni). The modeling based on the spin generation by electron-magnon scattering in bulk ferromagnets (namely, bulk spin pumping) well explains the dynamics and magnitude of the measured spin accumulation on Cu. (c) 2018 The Japan Society of Applied Physics